Perlindungan Hukum terhadap Hak Korban Tindak Pidana Pencabulan Anak di Tingkat Penyidikan dalam Perspektif Asas Equality Before the Law - Sela Nur Amalia Suprapto; Zarisnov Arafat; Muhamad Abas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study is based on the vulnerability of children as victims of sexual abuse, requiring strong juridical and procedural protection from the investigation stage to prevent revictimization and prolonged trauma. The research aims to evaluate the effectiveness of legal protections for child victims in Indonesia and assess how the principle of equality before the law ensures balanced justice for both victims and suspects. The method used is normative juridical research through library studies of primary, secondary, and tertiary legal sources, supported by interviews at the Women and Children Protection Unit (Unit PPA) of the Karawang Police Resort. Findings indicate that, normatively, Indonesia has a solid foundation through the 2025 Criminal Procedure Code, the Law on Witness and Victim Protection, the Child Protection Law, and Law No. 12 of 2022 on Sexual Violence Crimes, guaranteeing rights such as identity protection, expert accompaniment, and restitution. Practically, however, protection depends on adherence to cross-sectoral standard operating procedures, the involvement of certified female investigators, and coordination with institutions like the Regional PPA Unit, Social Services, and Correctional Guidance Office. The study concludes that restorative justice cannot be applied in child sexual abuse cases to protect the substantive rights of victims. Investigators face challenges in collecting psychologically affected testimony, limited eyewitnesses, and scarce evidence, resulting in incomplete protection. Therefore, strengthening formal judicial proceedings is essential to ensure justice for child victims.